Human cord blood leukocyte metallothionein-2A MRNA expression is associated with primiparaous and multiparous childbirth - Rahman, Mohammad Tariqur; Youssof, Ayman Lee; Abu Kassim , Noor Lide; Rashid, Siti Aishah; De Ley, Marc (2013)
Metallothionein (MT), a metal and stress-induced protein, provides transport and storage of metal ions. The current study analyzed the influence of human cord blood leukocyte [Zn] and gravida on leukocyte MT-2A mRNA expression. Samples (n= 47) were collected at the labor rooms of a Government hospital in Kuantan, Malaysia. [Zn] in plasma, erythrocytes, and leukocytes were measured by AAS (λ=213. 9 nm). MT-2A isoform specific mRNA was quantified by real-time PCR using total leukocyte RNA. Quantification of MT-2A gene transcription was normalized to the housekeeping gene, β-actin. Significant correlations were found between plasma [Zn] and erythrocyte [Zn] (r = .304; p< .05) and between leukocyte [Zn] and plasma [Zn] (r = .295; p< .05). Leukocyte [Zn] exhibited a significant correlation with MT-2A mRNA level (r = .765; p< .001). Higher levels of MT-2A mRNA was found in primiparous mothers (n= 16; M= 1.108, SD= 1.273) compared to multiparous mothers (n= 30; M= 0.581, SD= 0.711). Path analysis showed that leukocyte [Zn] has a greater influence (regression weight .84; p= .000) on MT-2A mRNA expression compared to gravida (regression weight -.18; p= .021). Finally it is concluded that, in addition to circulatory Zn, gravida contributes to the MT-2A mRNA expression.